Electron-beam-induced deposition and post-treatment processes to locally generate clean titanium oxide nanostructures on Si(100) - Schirmer, Michael; Walz, Marie-Madeleine; Vollnhals, Florian; Lukasczyk, Thomas; Sandmann, Achim; Chen, C.; Steinrück, Hans-Peter; Marbach, Hubertus (Nanotechnology, 2011)
We have investigated the lithographic generation of TiO nanostructures on Si(100) via electron-beam-induced deposition (EBID) of titanium tetraisopropoxide (TTIP) in ultra-high vacuum (UHV) by scanning electron microscopy (SEM) and local Auger electron spectroscopy (AES). In addition, the fabricated nanostructures were also characterized ex situ via atomic force microscopy (AFM) under ambient conditions. In EBID, a highly focused electron beam is used to locally decompose precursor molecules and thereby to generate a deposit. A drawback of this nanofabrication technique is the unintended deposition of material in the vicinity of the impact position of the primary electron beam due to so-called proximity effects. Herein, we present a post-treatment procedure to deplete the unintended deposits by moderate sputtering after the deposition process. Moreover, we were able to observe the formation of pure titanium oxide nanocrystals (>100 nm) in situ upon heating the sample in a well-defined oxygen atmosphere. While the nanocrystal growth for the as-deposited structures also occurs in the surroundings of the irradiated area due to proximity effects, it is limited to the pre-defined regions, if the sample was sputtered before heating the sample under oxygen atmosphere. The described two-step post-treatment procedure after EBID presents a new pathway for the fabrication of clean localized nanostructures. © 2011 IOP Publishing Ltd.

Probing the role of intercalating protein sidechains for kink formation in DNA - Sandmann, Achim; Sticht, Heinrich (PLoS ONE, 2018)
Protein binding can induce DNA kinks, which are for example important to enhance the specificity of the interaction and to facilitate the assembly of multi protein complexes. The respective proteins frequently exhibit amino acid sidechains that intercalate between the DNA base steps at the site of the kink. However, on a molecular level there is only little information available about the role of individual sidechains for kink formation. To unravel structural principles of protein-induced DNA kinking we have performed molecular dynamics (MD) simulations of five complexes that varied in their architecture, function, and identity of intercalated residues. Simulations were performed for the DNA complexes of wildtype proteins (Sac7d, Sox-4, CcpA, TFAM, TBP) and for mutants, in which the intercalating residues were individually or combined replaced by alanine. The work revealed that for systems with multiple intercalated residues, not all of them are necessarily required for kink formation. In some complexes (Sox-4, TBP), one of the residues proved to be essential for kink formation, whereas the second residue has only a very small effect on the magnitude of the kink. In other systems (e.g. Sac7d) each of the intercalated residues proved to be individually capable of conferring a strong kink suggesting a partially redundant role of the intercalating residues. Mutation of the key residues responsible for kinking either resulted in stable complexes with reduced kink angles or caused conformational instability as evidenced by a shift of the kink to an adjacent base step. Thus, MD simulations can help to identify the role of individual inserted residues for kinking, which is not readily apparent from an inspection of the static structures. This information might be helpful for understanding protein-DNA interactions in more detail and for designing proteins with altered DNA binding properties in the future.
EVALuna2:33714

Structural and functional dissection reveals distinct roles of Ca2+-binding sites in the giant adhesin SiiE of Salmonella enterica - Peters, Britta; Stein, Johanna; Klingl, Stefan; Sander, Nathalie; Sandmann, Achim; Taccardi, Nicola; Sticht, Heinrich; Gerlach, Roman; Muller, Yves; Hensel, Michael (PLoS Pathogens, 2017)

Structural and functional dissection reveals distinct roles of Ca2+-binding sites in the giant adhesin SiiE of Salmonella enterica - Peters, Britta; Stein, Johanna; Klingl, Stefan; Sander, Nathalie; Sandmann, Achim; Taccardi, Nicola; Sticht, Heinrich; Gerlach, Roman G.; Muller, Yves; Hensel, Michael (PLoS Pathogens, 2017)